Trendy w polskiej praktyce traktatowej po akcesji Polski do Unii Europejskiej - Kukulski, Ziemowit (Kwartalnik Prawa Podatkowego, 2015)
The article deals with trends in Polish treaty practice with the EU Member States after Poland’s accession to the EU. The Author analyses the influence of recommendation provided both by the OECD and UN Model Conventions on Polish treaty practice – as compared to the DTC’s concluded before the accession. In Author’s opinion, the main trends in Polish treaty practice after accession to the EU include: 1) renegotiation or changing by mean of amending protocol of many DTCs with the EU member states, 2) basing the Polish treaty practice on the OECD Model and 3) presence of a few characteristic recommendations for the UN Model in the Polish treaty practice (i.e. art. 12 § 1 and 2 – source taxation of royalties, art. 13 § 4 – immovable property clause, and art. 18A § 2 and art. 18B § 3 – exclusive source taxation of pensions paid within social security system). The Author notices also new trends in Polish treaty practice. These include: 1) incensement of the presence of switch-over clauses and other general and specific limitation of benefits clauses in Polish DTC’s recently adopted in order to eliminate tax avoidance and double non-taxation, 3) decrease of importance in case of professional services article and professors, teachers and researchers article – as compared to the DTC’s concluded by Poland before its accession to the EU. Although the Polish treaty network with the EU member states is completed, the Author comes to the conclusion that many of them still requires the improvement by introducing through amending protocols lacking instruments providing the mutual cooperation in tax matters between the two contracting states (i.e. arbitration as provided in art. 25 § 5 of the OECD Model [2008] or the assistance in collection of taxes – art. 27 of the OECD Model).